An Overview of the Lower and Upper Solutions Method with Nonlinear Boundary Value Conditions. (25th July 2010) - Cabada, Alberto
Abstract : The aim of this paper is to point out recent and classical results related with the existence of solutions of second-order problems coupled with nonlinear boundary value conditions.